Iodine- and TBHP-Promoted Acylation of Benzothiazoles under Metal-Free Conditions - Wang, Bin; Zhang, Qianwei; Guo, Zhongqi; Ablajan, Keyume (Synthesis, 2020)
A simple protocol for the synthesis of 2-acylbenzothiazoles using aryl ketones and benzothiazoles in the presence of I2 and TBHP is described. Acylation of the benzothiazoles is achieved through a sequence involving oxidation of the aryl ketone to an aryl glyoxal, ring-opening of the benzothiazole followed by condensation of the amino group with the aryl glyoxal, cyclization and oxidation. The method avoids the use of metals and toxic solvents. In addition, this protocol has the advantage of broad scope and provides good to excellent product yields.
Keywords: benzothiazoles; 2-acylbenzothiazoles; acylation; metal-free; 2-aminothiophenols